THE INFLUENCE OF THE LEADERSHIP OF THE HEAD OF TPQ IN MOTIVATING AND WORK CULTURE ON TEACHER PERFORMANCE IN TABANAN DISTRICT - Husnul Khotimah (Media Inovasi Pendidikan dan Publikasi, 2024)
This study aims to determine the influence of Head Leadership, motivation, and work culture partially and stimulants on the performance of TPQ teachers in Tabanan Regency. This research is an associative type of quantitative research. This study uses observation methods, questionnaires or questionnaires, and documentation. Data collection techniques using questionnaires or questionnaires,observation, and documentation. To prove and analyze the data, validity tests, reliability tests, classical assumption tests, multiple linear regression tests, as well as t (partial) and f tests (stimulants) were used. The test results showed that: 1) leadership, motivation, and work culture had a stimulating effect on the performance of TPQ teachers, with a value of Sig. 0.001 < 0.05. Because the Sig value is less than 0.05 then it can be concluded that Ha is accepted and H0 is rejected. 2) leadership has no effect on the performance of TPQ teachers partially, it was obtained that the sig value of the leadership style variable was 0.103 and the tcount value was 1.661 while the ttable was 2.005. 3) Motivation affects the performance of TPQ teachers partially, it was obtained that the SIG value of the work motivation variable was 0.001 and the calculation was 7.183 with a ttable of 2.005 4) Work Culture had an effect on the performance of TPQ teachers as well as partially, it was obtained that the SIG value of the work culture variable was 0.981 and the tcount was 0.024 with a ttable of 2.005.